Outcomes of Sequential Therapy With Tenofovir Alafenamide After Long-term Entecavir. (2nd June 2021) - Nguyen, Mindie H.; Atsukawa, Masanori; Ishikawa, Toru; Yasuda, Satoshi; Yokohama, Keisuke; Trinh, Huy N.; Arai, Taeang; Fukunishi, Shinya; Ogawa, Eiichi; Hsu, Yao-Chun; Maeda, Mayumi; Dang, Hansen; et al.
Abstract : INTRODUCTION: Entecavir (ETV) and tenofovir alafenamide (TAF) are both first-line hepatitis B virus (HBV) therapies, but ETV-to-TAF switch outcome data are limited. We aimed to assess outcomes up to 96 weeks after ETV-to-TAF switch. METHODS: ETV-treated (≥12 months) chronic hepatitis B patients switched to TAF in routine practice at 15 centers (United States, Korea, Japan, and Taiwan) were included. Primary outcome was complete viral suppression (CVS) rate (HBV DNA <20 IU/mL). RESULTS: We analyzed 425 eligible patients (mean age 60.7 ± 13.2 years, 60% men, 90.8% Asian, 20.7% with diabetes, 27% with hypertension, 14.8% with cirrhosis, 8.3% with hepatocellular carcinoma, and mean ETV duration before switch 6.16 ± 3.17 years). The mean baseline estimated glomerular filtration rate (eGFR) was 89 ± 19 (chronic kidney disease [CKD] stages: 55.6% stage 1, 35.7% stage 2, and 8.8% stages 3–5). CVS rate increased from 91.90% at switch (from 90.46% 24 weeks before switch) to 95.57% and 97.21% at 48 and 96 weeks after ( P = 0.03 and 0.02, respectively). Over the 96 weeks after switch, mean HBV DNA ( P < 0.001) but not alanine aminotransferase or CKD stage decreased. Between switch and 96-week follow-up, 11% (26/235) of CKD stage 1 patients migrated to stage 2 and 8% (12/151) of stage 2 patients to stages 3–5, whereas 18% (27/151) from stage 2 to 1, and 19% (7/37) from stages 3–5 to 2. On multivariable generalized estimated equation analysis adjusted for age, sex, hypertension, diabetes, and cirrhosis, baseline eGFR, age ( P < 0.001), and CKD stages 2 and 3–5 (vs 1) (both P < 0.001) were associated with lower follow-up eGFR. DISCUSSION: After an average of 6 years on ETV, CVS increased from 91.9% at TAF switch to 97.2% at 96 weeks later.